ANALISIS HARGATERHADAP ROOM OCCUPANCY HOTELDAN PENGINAPANDI KOTA PANGKALPINANG - Juhari Juhari (Jurnal Bisnis Darmajaya, 2016)
The purpose of this study was to determine the effect on the price of the analysis room occupancy in hotels and inns in Pangkalpinang. Methods of data collection in this research is using secondary data regarding the price (room rate) and the occupancy rate of rooms (room occupancy) at 13 hotels and 7 hotels in Pangkalpinang. Methods of data analysis using simple regression analysis. The findings of this study are positive and significant effect on the price of the room occupancy. Meanwhile, based on the results of the analysis of the correlation coefficient and determination, influence the price of the room occupancy hotels in Pangkalpinang is very strong, of 74.8%, while the remaining 25.2% is influenced by other factors such as service quality, customer satisfaction, promotions and so were not examined in this study. Keywords: Price and Room Occupancy